Wrigley regulars : finding community in the bleachers - Swyers, Holly (University of Illinois Press, 2010)
Holly Swyers turns to the bleachers of Chicago's iconic Wrigley Field in this unique exploration of the ways people craft a feeling of community under almost any conditions. Wrigley Regulars examines various components of community through the lens of "the regulars," a group of diehard Chicago Cubs fans who loyally populate the bleachers at Wrigley Field. In a time when many communities are perceived as either short-lived or disintegrating, Swyers examines the conditions, practices, and behaviors that help create and sustain the experience of community. At Wrigley Field, these practices can include the simple acts of scorecard-keeping and gathering at the same location before each game or insisting on elaborate rules of ticket distribution and seating arrangements, as well as more symbolic behaviors and superstitions that link the regulars to each other. A bleacher regular herself, Swyers uses a qualitative approach to define community as the ways in which people arrive at an awareness of themselves as a group with a particular relationship to the larger world.